Water content in hydrated ethanol fuel measured by a photothermal chamber with a transparent transducer - Omido, Cleidson R. [UNESP]; Oliveira, Samuel L.; Lima, Juliete R.; Magalhaes, Keurison F.; Carvalho, Aparecido A. de [UNESP]; Kitano, Claudio [UNESP] (Elsevier B.V., 2015)
A photothermal chamber with a transparent transducer and a 1450 nm laser were used to measure the water content of hydrated ethanol biofuel. The values of water content in the fuel samples assessed using the photothermal chamber were compared with reference values certified by Karl-Fischer titration. The results indicate good agreement between these two methodologies. Detection thresholds of 0.73 and 0.89 (% w/w) and sensitivity of 0.039 and 0.014 mV/(% w/w) were assessed at the laser powers of 340 and 125 mW, respectively. This study proves that the analytical approach based on the photothermal chamber with a transparent transducer is convenient to determine the water content in ethanol fuel because it is capable of providing reliable results in a quick and accurate way. (c) 2015 Elsevier Ltd. All rights reserved.
Keywords: Ethanol; Water; Fuel; Photothermal technique